The Effect Of Transition Action Details (TAD) Strategy Toward Students’ Writing Ability Of Recount Text At Senior High School 6 Pariaman - Irna Wahyuni (Jurnal Kajian Ilmu Pendidikan (JKIP), 2021)
The purpose of this research was to find out the Effect of Transition Action Details strategy toward Students’ writing ability of recount text to the first Grade at SMAN 6 Pariaman. The kind of This researches in the form of experiment, especially pretest and posttest control group design. The research population was all students in class X IPS SMAN 6 Pariaman school year 2018/2019 that consist of 100 students. The samples were X IPS1 class as the experimental class that consist of 25 students and X IPS2 class as the control class that consist of 25 students. This research used cluster random sampling technique.Experimental class was taught by using transition action details, and control class was taught by using conventional strategy. The instrument of collecting the data that used by the researcher was writing test. The technique of analyzing data was the hypothesis test was t-test formula, which was used test the difference in mean and standard deviation of the two samples.Based on the analysis of data obtained, tcalculate=3,33 and ttable=1.67 .Because tcalculate (3,33) > ttable (1.67), then H0 was rejected and H1 was accepted, it can be concluded that the application of Transition Action Details strategy provides a significant effect on students’ writing ability of class X rather than conventional strategy at SMAN 6 Pariaman. Key words: transition action details, wrriting, recount text